Preferences for Japanese Baby Powdered Milk in Vietnam: Choice Experiment and Structural Equation Modelling Approaches - Dinh, Linh Dieu; Lee, Brice Tseen Fu (Efficient: Indonesian Journal of Development Economics, 2025)
The Vietnamese market has seen a growing influx of Japanese baby powdered milk. This study investigates key product attributesthat influence Vietnamese consumers’ purchase intentions and the impact of Japanese brand origin compared to domestic and other imported brands. Although consumer behavior studies exist, research on Japanese baby powdered milk in Vietnam is limited. Data from 109 social media responses were analyzed using a Choice Experiment and Structural Equation Modeling. Results reveal that Vietnamese parents show a strong preference for Japanese brands due to attributes such as nutrition labels and safety certificates, which significantly affect purchase decisions. Price sensitivity is also observed but is less critical comparedto safety and nutritional value. This study highlights the importance of leveraging brand origin in marketing strategies for Japanese companies targeting Vietnam. Future research should explore additional attributes, such as flavor and health benefits, and examine the roleof ethnocentrism in consumer preferences.